The Frequency Characteristics Simulation of Traveling Wave Thermo-Acoustic Engine - Ma Lili; Xia Jiakuan; Guo Tie (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The frequency characteristics of thermo-acoustic engine mainly depend on the internal working medium and device structure. The linear resonant system is consisted of ironless permanent magnet linear synchronous motor and the resonant spring. Through the analysis of thermo-acoustic power generation system model, the parameters of linear resonant system are determined by building a mathematical model of linear resonant system. Combined with modern control theory and robust control theory, a robust position controller was design. The theoretical analysis and simulation proved that the controller can make the linear resonance system obtain higher frequency response and displacement accuracy. Controller response time and output is more stable, the controller meets the necessary optimal control. The controller is suitable for thermal acoustic generator control system with high reliable and robust quantitative. The designed linear resonance system can well simulate the frequency characteristics of thermo-acoustic engine. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2400